2001
DOI: 10.1002/esp.253
|View full text |Cite
|
Sign up to set email alerts
|

Initial hydrologic and geomorphic response following a wildfire in the Colorado Front Range

Abstract: A wildfire in May 1996 burned 4690 hectares in two watersheds forested by ponderosa pine and Douglas fir in a steep, mountainous landscape with a summer, convective thunderstorm precipitation regime. The wildfire lowered the erosion threshold in the watersheds, and consequently amplified the subsequent erosional response to shorter time interval episodic rainfall and created both erosional and depositional features in a complex pattern throughout the watersheds.The initial response during the first four years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

23
391
3
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 392 publications
(420 citation statements)
references
References 40 publications
23
391
3
3
Order By: Relevance
“…At larger scales, such as entire watersheds or multiple watershed systems, studies of post-fire erosion rates have shown incompatible conclusions (Moody and Martin, 2001;Owens et al, 2013;Smith et al, 2011), though this is most likely due to the variability of precipitation events and general climate patterns (Moody et al, 2013). In terms of water quality, contaminant levels can be dramatically increased for many years after a wildfire in both soil (Burke et al, 2010) and stream systems (Emelko et al, 2011;Stein et al, 2012;Burke et al, 2013), increasing the workload on source water protection organizations in communities reliant upon burned watersheds for drinking and agricultural water.…”
Section: Introductionmentioning
confidence: 99%
“…At larger scales, such as entire watersheds or multiple watershed systems, studies of post-fire erosion rates have shown incompatible conclusions (Moody and Martin, 2001;Owens et al, 2013;Smith et al, 2011), though this is most likely due to the variability of precipitation events and general climate patterns (Moody et al, 2013). In terms of water quality, contaminant levels can be dramatically increased for many years after a wildfire in both soil (Burke et al, 2010) and stream systems (Emelko et al, 2011;Stein et al, 2012;Burke et al, 2013), increasing the workload on source water protection organizations in communities reliant upon burned watersheds for drinking and agricultural water.…”
Section: Introductionmentioning
confidence: 99%
“…There is a shortage of quantitative measurements of the downstream extent and persistence of effects of water and sediment conveyed from burned catchments. In Colorado, detailed measurements of the post-fire bathymetry of a water supply reservoir allowed the calculation of the volume of sediment transported from two burned catchments (one 18 km upstream, the other 5 km upstream) [55]. Measurements after a fire in California, USA detected changes in suspended sediment in a reservoir 160 km downstream of the burned area [65] and a recent study in New Mexico [49] detected elevated values of specific conductance and small changes in turbidity at a site approximately 120 km downstream of a burned area during and four months after the largest fire recorded in the state (approx.…”
Section: Introductionmentioning
confidence: 99%
“…In the Colorado Front Range the mean sediment yield from four 1 m Gerlach traps on unburned hillslopes was only 0Ð3 Mg ha 1 year 1 (Moody and Martin, 2001). On unburned 1 m 2 plots a simulated rainfall of 76 mm h 1 generated a mean sediment yield of only 0Ð7 Mg ha 1 (Benavides-Solorio andMacDonald, 2001, 2002).…”
Section: Introductionmentioning
confidence: 99%